Numerical analysis of seawater desalination based on a solar chimney power plant. (15th December 2017) - Ming, Tingzhen; Gong, Tingrui; de Richter, Renaud K.; Cai, Cunjin; Sherif, S.A.
Highlights: Seawater droplets are sprayed for evaporation at the chimney inlet. 3D model was developed for the air cooling and condensation inside the chimney. The condensation level can be greatly reduced by the humidification. The humidification is conductive to improving the system desalination efficiency. Abstract: In this paper, the desalination performance of a plant variant with the same size as the Manzanares pilot model was numerically investigated. A three-dimensional compressible flow and heat transfer model has been developed, describing the air cooling process along the chimney and the associated condensation. In this plant variant, instead of installing the turbine, water droplets were sprayed for evaporation at the bottom of the chimney, and thus airflow was subjected to humidification. Results show that with increased mass fraction of water in the air, the influence of the microclimate on the local environment will also increase. The evaporation of the droplets improves the relative humidity of the air within the chimney, and the condensation level can thus be greatly reduced. Moreover, the freshwater output increases with increasing amount of water sprayed, which is beneficial for the improvement of the desalination efficiency of the system.